HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DENGAN KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH - -, Lutfi Su'adah; -, Nana Novariana; Pratiwi Putri, Dian Utama (Jurnal Ilmiah Kesehatan Media Husada, 2025)
Introduction: Anemia in pregnant women is a public health problem that needs serious attention. Pregnant women's knowledge about anemia can affect their compliance in consuming blood supplement tablets. The purpose of this study is to determine the relationship between pregnant women's knowledge about anemia and compliance with consuming blood supplement tablets at one of the health centers in South Lampung Regency in 2024. Method: This type of study was quantitative using a cross-sectional design. The study population is 751 pregnant women who receive blood supplement tablets in the working area of the Health Center in 2024. The sample was taken by purposive sampling technique and totaled 88 people. Data were collected through questionnaire sheets and analyzed using the chi-square test. Results: The study showed that most pregnant women (83.0%) had good knowledge about anemia. As many as 80.7% of pregnant women are obedient in consuming blood supplement tablets. Conclusion: from the results of the analysis, it was obtained that the P-value was 0.001 < (smaller) than 0.05 that there was a relationship between pregnant women's knowledge about anemia and compliance with the consumption of blood supplement tablets.